Odpowiedzi

2010-03-16T12:21:07+01:00
Y=1/2 x -2
A=(1/3,?)
y=?
y=1/2*1/3-2
y=1/6-2
y=-1i5/6

B=(?,O)
x=?
0=1/2x-2
-1/2x=-2-0
x=4

C=(O,?)
y=?
y=1/2*0-2
y=0-2
y=-2

D=(?,-3)
x=?
-3=1/2x-2
-1/2x=-2+3
-1/2x=1
x=-2
2010-03-16T12:28:08+01:00
Y=1/2x-2
Podstawiając do równania za zmienną x pierwszą współrzędną
A=(1/3,-1 5/6)
B=(4,O) C=(O,-2) D=(-2,-3)
2010-03-16T12:36:47+01:00
A
x=⅓ y=? y=½x-2=½×⅓-2=⅙-2=1⅚ A=(⅓;1⅚)

B
y=0 x=? 0=½x-2 czyli ½x=2 a więc x=4 B=(4;0)

C
x=0 y=? y=½×0-2=-2 C=(0;-2)

D
x=? y=-3 -3=½x-2 ½x=-3+2 ½x=-1 x=-2 D=(-2;-3)